Penerapan Konseling Traumatik Dalam Menangani Gangguan Psikologis Masyarakat Pada Bencana Alam ( Pendekatan Cognitif-Behavior Therapy) - zulkarnaen zulkarnaen; ramli ramli (Institut Agama Islam (IAI) Nurul Hakim, 2023)
Indonesia is one of the countries that is frequently hit by natural disasters, and many of these disasters cause many victims. And many survivors experienced psychological trauma. Departing from these facts, the government should prepare individuals who are skilled in dealing with traumatic cases experienced by victims of natural disasters. Trauma is an emotional condition that develops after a traumatic event that is unpleasant, sad, scary, worrying, and upsetting, such as events: rape, fighting, physical violence, accidents, natural disasters, and certain events that stress the counselee's mind. Counseling in traumatic cases is defined as therapeutic assistance directed at changing the attitudes and behavior of the traumatized counselee, carried out face-to-face between the counselee and the counselor, through interview techniques with the counselee so that the problems they are experiencing can be resolved. One of the therapeutic approaches that can be applied by professional counselors is Cognitive Behavior Therapy (CBT).